2017
DOI: 10.18632/oncotarget.17424
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of circulating microvesicles derived from myocardial ischemic rats on apoptosis of cardiomyocytes in myocardial ischemia/reperfusion injury

Abstract: ObjectiveTo investigate the effects of circulating microvesicles derived from myocardial ischemia (I-MVs) on apoptosis in myocardial ischemia/reperfusion (I/R) injury in rats.MethodsI-MVs from rats undergoing myocardial left anterior descending (LAD) coronary artery ligation were isolated by ultracentrifugation from circulating blood and characterized by flow cytometry. I-MVs were administered intravenously (4.8 mg/kg) at 5 min before reperfusion procedure in I/R injury model which was induced by 30-min of isc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…MVs are cystic vesicles secreted from cells under stimulation or apoptosis, which can be involved in the pathogenesis of various diseases. Recent studies have demonstrated that circulating MVs are responsible for the transmission of IPC signals that elicit cardioprotection [5,6]. In the present study, IPC-MVs and Sham-MVs in circulation were successfully obtained, and the total amount of IPC-MVs was slightly higher than that of Sham-MVs.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…MVs are cystic vesicles secreted from cells under stimulation or apoptosis, which can be involved in the pathogenesis of various diseases. Recent studies have demonstrated that circulating MVs are responsible for the transmission of IPC signals that elicit cardioprotection [5,6]. In the present study, IPC-MVs and Sham-MVs in circulation were successfully obtained, and the total amount of IPC-MVs was slightly higher than that of Sham-MVs.…”
Section: Discussionsupporting
confidence: 44%
“…It is wellknown that ischemic preconditioning (IPC) is one of the most powerful cardioprotective interventions to reduce myocardial I/R injury [2], which could induce extracellular vesicles (EVs) such as microvesicles (MVs) and exosomes release and changes in microRNA (miRNA) expression in cardiomyocytes [3,4], but the underlying mechanism remains elusive. Recently, it has been shown in our study that circulating MVs released from the heart after IPC (IPC-MVs) are required for cardioprotection by IPC [5] and that IPC-MVs could protect against myocardial I/R injury by regulating GRP78 and CHOP expression in endoplasmic reticulum pathway [6]. However, elucidating the protective mechanisms of IPC-MVs needs further molecular experimentation.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…MSC-derived MVs were able to face the detrimental effects of ischemia and reperfusion (I/R) injury in the kidney ( 266 ). Similarly, MVs derived from myocardial ischemia could protect hearts from I/R injury in rats through calcium regulatory proteins to alleviate intrinsic myocardial mitochondrial and endoplasmic reticulum apoptotic pathways ( 267 ). Interestingly, the effect of cardiosphere-derived cells (CDC) on the therapeutic regeneration of the infarcted myocardium shown in a clinical trial ( 268 ) seems to be mediated by CDC-derived extracellular vesicles ( 269 ).…”
Section: Pharmacological and Non-pharmacological Interventionmentioning
confidence: 99%
“…In contrast, recent studies by Ma et al (2015) have shown that transfusion of microvesicles isolated from rats immediately, but not 6 hours after a hind limb ischemia-induced RIPC into recipient rats exposed to heart I/R injury, resulted in an increase in platelet-derived particles in blood associated with reduction in infarct size and improved functional recovery of hearts. The role of IPC-induced circulating microvesicles in cardioprotection against myocardial I/R injury was also confirmed in the study of Wang et al (2016) where authors injected these isolated particles after coronary occlusion-induced IPC to recipient rats that were consequently exposed to MI and found that myocardial infarct size and cardiomyocyte apoptosis as well as LDH release were reduced. In addition, they found a decreased expression of Bax and activity of caspase 3 and increased expression of Bcl-2 and Bcl-2/Bax ratio after IPC-microvesicles treatment suggesting cardioprotective effects of IPC-microvesicles through inhibition of apoptosis induction.…”
Section: Role Of Microvesicles In Ricmentioning
confidence: 74%